Feasibility and marketing studies of health sciences librarianship education programs. - Lipscomb, C E (1999)
The University of North Carolina at Chapel Hill evaluated five curricular models designed to improve education for health sciences librarianship. Three of the models enhanced existing degree and certificate programs, and two were new programs for working information professionals. Models were developed with input from experts and a Delphi study; the marketability of the models was tested through surveys of potential students and employers; and recommendations were made as a guide to implementation. The results demonstrated a demand for more specialized curricula and for retraining opportunities. Marketing data showed a strong interest from potential students in a specialized master's degree, and mid-career professionals indicated an interest in postmaster's programs that provided the ability to maintain employment. The study pointed to the opportunity for a center of excellence in health sciences information education to enable health sciences librarians to respond to their evolving roles.